Managing at Maximum Sustainable Yield does not ensure economic well‐being for artisanal fishers - Alfredo Giron‐Nava; Andrew F. Johnson; Andrés M. Cisneros‐Montemayor; Octavio Aburto‐Oropeza (Fish and Fisheries, 2019)
Maximum Sustainable Yield ( MSY ) is a common target for fisheries aiming to achieve long‐term ecological sustainability. Although achieving MSY may ensure the long‐term sustainability of fish populations, we ask whether it will provide economic security for fishers. Here we use 16 years of daily landing records to estimate potential catches and revenues per capita if fisheries were exploited at MSY in 11 subregions across Mexico. We then compare fishers’ estimated revenues per capita against national poverty limits at the household level. Our results show that even if MSY is reached in artisanal fisheries, the overcapacity of fleets and the dissipation of rents threatens the economic well‐being of fishers and their families, pushing revenues per capita below poverty levels. Our work demonstrates the importance of resolving the trade‐offs between achieving economic, social and environmental objectives when managing for the long‐term sustainable use of natural resources.